Consequences of Increases in Ambient Temperature and Effect of Climate Type on Digestibility of Forages by Ruminants: A Meta-Analysis in Relation to Global Warming - Mehluli Moyo; Ignatius Nsahlai (Animals, 2021)
This meta-analysis evaluated the effects of ruminant feeding type, ambient temperature (AT), and climatic region on the rumen digestibility of feeds. A dataset on nylon bag degradability parameters bearing the chemical composition of roughages, grains, leaves, stems, fruits, concentrates and diets given to animals, climate type, and AT were compiled. Data were analysed using mixed model regression and simple linear regression methodologies. Negative correlations between AT and degradability parameters were observed. Potential degradability (PD) and slowly degradable fraction (‘b’) were higher for concentrates and mixed diets compared to roughages. Intermediate feeders had slower rates of degradation (‘c’) compared to grazers. Potential degradability was highest for studies carried out in cold and temperate climates compared to tropical and arid climates. A 1 °C increase in AT decreased PD by 0.39% (roughages), 0.76% (concentrates), and 2.41% (mixed diets), with an overall decrease of 0.55% for all feed types. The “b” fraction decreased by 0.1% (roughages), 1.1% (concentrates), 2.27% (mixed diets), and 0.35% (all feed types) for every 1 °C increase in AT. Increasing AT by 1 °C increased the neutral detergent fibre content of feeds by 0.4%. In conclusion, increases in AT increased the neutral detergent fibre content of feeds, lowering PD, “b”, and “c” of dry matter in the rumen.